Pelatihan pembuatan masker kain dalam upaya mencegah penularan Covid 19 di Surakarta - Eko Meiningsih Susilowati (Universitas Hamzanwadi, 2021)
Since 2020, Indonesia has been hit by the Covid-19 pandemic, so people must implement health protocols. The government has made rules so that people are required to wear masks. This regulation had made the mask are rare, and the price is very high. Based on this situation, this activity aims to train the people of Kampung Tegalharjo, Jebres, Surakarta to make masks and sell these masks. On August 9, 2020, the activity was carried out in Tegalharjo Village, Jebres District, Surakarta City. The method used is by way of lectures, practice, and discussion. As a partner in this activity, only one group of housewives in Tegalharjo Village totaled 12 people. The results obtained are that as many as 80% of partners in the village can make health masks made of cloth well and can sell them or market them for profit and can increase income. So that the sales proceeds can help improve the welfare of life. Henceforth, in order to be able to market their products more widely and sell more online.